Functionalization of g-C3N4 for efficient solar fuels production - Koh, Chin Sing (Nanyang Technological University, 2020)
One of the most important resources on our planet is fossil fuel. It is mostly used as gasoline for vehicles, making plastic and polyester material, and lastly, generate electricity. However, fossil fuels are non-renewable energy and produce greenhouse gases which will enhance global warming. Research has been done to lower the speed of global warming and it is doable by lowering the production of CO2. A good photocatalyst that can cause photocatalytic reduction of CO2 is g-C3N4. g-C3N4 is a polymer make up of earth-abundant materials, carbon and nitrogen, it has a low band gap, ability to absorb light from visible light range and it can be used to generate solar fuels. Ruthenium (Ru) complexes are highly active catalysts for hydrogen transfer. Hydrogen can be moved intramolecularly from hydrogen donor to acceptor in terms of hydride, or proton, after which cyclisation will take place to furnish the cyclic products in developments featuring high atom economy. The purpose of this project is to analyse the effect of g-C3N4 with different materials for photocatalytic reduction of CO2 into methane (CH4) under visible light irradiation. The composite includes copper-modified carbon nitride (GCN-Cu), ruthenium-modified carbon nitride (GCN-Ru), and lastly ruthenium-copper-modified carbon nitride (GCN-RuCu). This report will also include the functionalization of g-C3N4 could serve as a further improvement to the photocatalytic reduction of CO2 into CH4.